Splenic artery aneurysm: a case report with review of literature - Lakshmi, A. Bhagya; Begum, Shaik Ayeesha; Reddi, Bhavani Rao; Rao, K. Janardhan (International Journal of Research in Medical Sciences, 2017)
Splenic Artery Aneurysm (SAA) is very rare in occurrence and they occur in approximately 1% of the population and are usually an incidental finding,but the necropsy studies have given rates as high as 10%. For its rarity in occurrence here we present a case of splenic artery aneurysm in a 40 year old alcoholic presenting with upper and lower gastrointestinal bleeding. He was diagnosed as splenic artery aneurysm on CT scan and confirmed by laparotomy and pathological examination.